Munc18-1 is crucial to overcome the inhibition of synaptic vesicle fusion by αSNAP - Karolina P. Stepien; Eric A. Prinslow; Josep Rizo (Nature Communications, 2019)
Munc18-1 and Munc13-1 are key for the exquisite regulation of neurotransmitter release. Here biophysical experiments show how αSNAP inhibits liposome fusion mediated by the neuronal SNAREs and how Munc18-1 overcomes this inhibition, ensuring that release depends on Munc18-1 and Munc13-1.